Professional-Competence-Based Model of Classroom Action Research Training Management for Islam Religion Education Teachers of Senior High School - Cholid, Nur; Masrukhi, Masrukhi; Rusdarti, Rusdarti; Sugito, Ari Tri (Universitas Negeri Semarang, 2018)
A number of efforts have been made to improve the quality of teachers, such as providing training on curriculum, methods of learning, and further study for those who have not completed their undergraduate program. However, these efforts do not seem to be maximally successful in improving the quality of the learning process and outcomes. Therefore, training is needed in order to improve the professional competence of the teachers through classroom action research training. This research aimed to yield a product, that is the management model of classroom action research training for Islam Religion Education Teachers of Senior High Schoolof in Semarang City which is packaged in the form of a classroom action research management training manual for teachers as guidebooks for instructors and trainees to improve their professional competence. This study utilized a Research and Development approach which was preceded by a qualitative descriptive method. This method was used as a preliminary to obtain data on how to implement the training that has been running for this. A preliminary study revealed what the problem was with the training. The results show that the development of the management model of classroom action research training was carried out in accordance with the development procedures which include preliminary research, analysis, production/development, and revision, while the product was evaluated in accordance with the development of evaluation procedures.